Growth of Nano (Na)V2O5 from NaBH4 and V2O5 at Room Temperature - Aksu1, Mecit (Asian Journal of Chemistry, 2014)
In this work V2O5 was reduced to sodium intercalated NaV2O5 with NaBH4 in pyridine-water solvent. Techniques to investigate the composition, crystallinity and morphology of products as prepared include field emission scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray powder diffraction inductively coupled plasma-atomic emission spectroscopy. Unit cell parameters are a = 11.28, b = 3.583, c = 4.76 Å and a = b = g = 90°. Mean crystallite size was calculated to be 4.8 nm.